Ethylene responsive factors in the orchestration of stress responses in monocotyledonous plants - Dey, Sanjukta; Corina Vlot, A. (Frontiers in Plant Science, 2015)
The APETALA2/Ethylene-Responsive Factor (AP2/ERF) superfamily of transcription factors regulates physiological, developmental and stress responses. Most of the AP2/ERF transcription factors belong to the ERF family in both dicotyledonous and monocotyledonous plants. ERFs are implicated in the responses to both biotic and abiotic stress and occasionally impart multiple stress tolerance. Studies have revealed that ERF gene function is conserved in dicots and monocots. Moreover, successful stress tolerant phenotypes are observed on expression in heterologous systems, making ERFs promising candidates for engineering stress tolerance in plants. In this review, we summarize the role of ERFs in general stress tolerance, including responses to biotic and abiotic stress factors, and endeavor to understand the cascade of ERF regulation resulting in successful signal-to-response translation in monocotyledonous plants.